Pemodelan Data Warehouse Distribusi Produk di PT. X - Susanto, Rani; M, Tati Harihayati (Universitas Nusantara PGRI Kediri, 2019)
The purpose of this study is to provide an overview of the Head of Distribution of PT. X to support product distribution monitoring activities in terms of the number of products to be distributed to each branch office as needed. The problem that occurs is the large number and diversity of products required where each branch office is located far apart, cause the company difficulty in collecting product data that functions for the monitoring process. The solution to this problem is there needs a model that can be used to collect all the necessary data for monitoring product distribution using the Data warehouse method. This method is used to collect diverse data into a storage area so that users can quickly analyze the data needed. OLTP is part of the Data Warehouse, which is the initial stage of modeling data sources, then with ETL processes, which are the basis for modeling data warehouse schemes. So, this model can be used as a reference to produce useful information for managerial parties PT. X in the next study.